On Purely Hermitian R-complex Finsler Space with (Î±, Î²)-Metric - Venkatesha, K. S.; Narasimhamurthy, S. K.; Chandru, K. (IndoMS, 2021)
In the present paper we established some interesting results on purely Hermitian R-complex Finsler space with (Î±, Î²)-metrics, Firstly we characterize the conditions for the (Î±, Î²)-metric F = p Î±2 + ÎµÎ²2 to be a purely Hermitian. Then determined the fundamental metric tensor, its inverse and determinent of the above metric. Further obtained Chern-Finsler connection coefficients and analysed necessary conditions under which an purely Hermitian R-complex Finsler space with (Î±, Î²)-metric to be Berwald, Kahler and strongly Kahler also given some examples.